Informação e contexto: uma análise arqueológica - Pacheco, Leila Maria Serafim (1992)
Knowing information as an artefact, the author uses archaeological dimensions - space, time and form - and an extra dimension, silence, to demostrate that information meaning changes when any one of such dimensions change. Arguing that information conveys representation from a context to another one, she concludes that information implies on recontextualization.